2019
DOI: 10.5194/acp-2019-828
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cloud Condensation Nuclei properties of South Asian outflow over the northern Indian Ocean during winter

Abstract: <p><strong>Abstract.</strong> Extensive measurements of cloud condensation nuclei (CCN) and condensation nuclei (CN) concentrations in the South Asian outflow to the northern Indian Ocean were carried out on board an instrumented research vessel, as part of the Integrated Campaign for Aerosols, gases and Radiation Budget (ICARB) during winter season (January–February 2018). Measurements include a north-south transect across the South Asian plume over the … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 25 publications
(55 reference statements)
1
5
0
Order By: Relevance
“…×10 3 ) by Li et al (2015) in the continental atmosphere of Qingdao in May 2013, however, the increment of Nccn with the increase of SS was much weaker in our study, resulting in on average of 36% smaller in Nccn under SS of 0.4% to 1.0% compared to Li et al (2015). Consistently, the sensitivity differences of Nccn to SS between relatively clean (i.e., Ncn (8.1 ± 4.4×10 3 ) in this study) and polluted (with Ncn of 1.8 ± 1.4×10 4 cm -3 ) environment in Li et al (2015) is also reported by Nair et al (2019) In addition, Nccn at SS from 0.1% to 1.0% during the period with high NH4 + (17:00 LT on DOY 114 to 10:00 LT on DOY 120) is statistically significant higher (P<0.01) in comparison to the poor NH4 + period (11:00 LT on DOY 120 to 7:00LT on DOY 136; Fig. 3b).…”
Section: Spatiotemporal Variations In Ambient Nccn During the Cruise Periodsupporting
confidence: 84%
“…×10 3 ) by Li et al (2015) in the continental atmosphere of Qingdao in May 2013, however, the increment of Nccn with the increase of SS was much weaker in our study, resulting in on average of 36% smaller in Nccn under SS of 0.4% to 1.0% compared to Li et al (2015). Consistently, the sensitivity differences of Nccn to SS between relatively clean (i.e., Ncn (8.1 ± 4.4×10 3 ) in this study) and polluted (with Ncn of 1.8 ± 1.4×10 4 cm -3 ) environment in Li et al (2015) is also reported by Nair et al (2019) In addition, Nccn at SS from 0.1% to 1.0% during the period with high NH4 + (17:00 LT on DOY 114 to 10:00 LT on DOY 120) is statistically significant higher (P<0.01) in comparison to the poor NH4 + period (11:00 LT on DOY 120 to 7:00LT on DOY 136; Fig. 3b).…”
Section: Spatiotemporal Variations In Ambient Nccn During the Cruise Periodsupporting
confidence: 84%
“…The cruise track and sampling locations are shown in Figure 1. Detailed descriptions about the cruise track and prevention of possible contamination from the ship exhaust are available elsewhere (Nair et al., 2020). Calm and low winds (<5 ms −1 ) were noted during the sampling period.…”
Section: Methodsmentioning
confidence: 99%
“…During this season, north-easterly winds are persistent and convection over the continental source regions is concealed by largescale subsidence, thus restraining the vertical dispersion of pollutants. The studies as part of ICARB-2018 documented the CCN activity properties of SA outflow over the IO (Nair et al, 2020), bulk chemical composition , tropospheric carbon monoxide (CO) distribution (Girach et al, 2020), near-surface aerosol mass concentrations and its size…”
Section: Accepted Articlementioning
confidence: 99%
See 1 more Smart Citation
“…In India, several intensive field campaigns such as the Indian Ocean Experiment (INDOEX; Ramanathan et al, 2001), Indian Space Research Organization (ISRO)-Geosphere-Biosphere Programme (GBP)-Land campaign II (Tripathi et al, 2006;Tare et al, 2006), and Integrated Campaign for Aerosols, gases, and Radiation Budget (ICARB; Moorthy et al, 2008;Nair et al, 2020;Kompalli et al, 2020) have measured sub-micron particle number size distributions (PNSDs). There are also short-and long-term field observations of sub-micron PNSDs in a variety of diverse locations in India (Hyvärinen et al, 2010;Kanawade et al, 2014a;Shika et al, 2020;Tripathi et al, 1988;Komppula et al, 2009;Singh et al, 2004;Moorthy et al, 2011;Babu et al, 2016;Kompalli et al, 2018).…”
Section: Introductionmentioning
confidence: 99%